ENHANCING UNIVERSAL PRECAUTION IMPLEMENTATION IN SELF-EMPLOYED MIDWIFERY: KEY INFLUENCING FACTORS IN CHILDBIRTH ASSISTANCE: ENHANCING UNIVERSAL PRECAUTION IMPLEMENTATION IN SELF-EMPLOYED MIDWIFERY: KEY INFLUENCING FACTORS IN CHILDBIRTH ASSISTANCE - hesti, Novria Hesti; Zulfita (International Health Sciences Journal, 2024)
ABSTRACT Background: The main causes of maternal death in Indonesia in 2019 are bleeding, hypertension during pregnancy, infections, metabolic problems and others. Approximately 25-50% of maternal deaths are caused by problems related to pregnancy, childbirth and the puerperium. Universal Precaution is an action to control infection that must be carried out by all health workers in order to reduce cases of the spread of infection. Objective: To find out the factors that influence the implementation of universal precautions in delivery assistance by midwives in the Midwife Independent Practice (PMB) in Padang city. Methods: This type of research is analytic with a cross-sectional study design. The study population is all midwives who have PMB in the city of Padang. The sample of this research was midwives who had PMB who served delivery assistance, totaling 35 respondents. Sampling using non-probability sampling technique, namely Total Sampling. Data collection was carried out using a questionnaire and the statistical test used was the Chi Square Test. Results: More than half of the respondents 54.3% had good universal precautions in childbirth assistance, more than half of the respondents 57.1% had a high level of knowledge, more than half of the respondents 68.6%, had a positive attitude more than half of the respondents 54, 3% have less time working, more than half 62.9% have complete facilities and infrastructure. There is a relationship between the level of knowledge and the implementation of universal precautions in delivery assistance with the result pvalue = 0.005 <0.05. There is no relationship between attitude and implementation of universal precautions pvalue=0.150, length of work and implementation of universal precautions pvalue=0.640, availability of facilities and infrastructure with implementation of universal precautions pvalue=0.149. Conclusion: More than half of the respondents have implemented universal precautions both in childbirth assistance, more than half of the respondents have a high level of knowledge, more than half of the respondents have a positive attitude, more than half of the respondents have worked less long, more than half have complete facilities and infrastructure . There is a relationship between the level of knowledge and the implementation of universal precautions in childbirth assistance. There is no relationship between attitude, length of work, availability of facilities and infrastructure with the implementation of universal precautions in childbirth assistance.